Performance of resident nurses in obstetrics on childbirth care - Santana,Ariane Teixeira de (2019)
Abstract Objectives: to describe good practices on childbirth care and obstetric interventions performed by resident nurses in obstetrics during the obstetric childbirth risk at a public maternity hospital in Salvador. Methods: a descriptive cross-sectional study with a quantitative approach, based on the of 102 parturients, between February and April 2016. The data collection was performed through the collection of information on clinical files for analysis by using descriptive statistics with absolute and relative frequencies for the evaluated categorical variables. Results: it was observed that 100.0% of the women used some kind of non-pharmacological method for pain relief, although the method of choice was to take a hot bath; 99.0% of the women drank liquids; 94.0% had the presence of a companion of free choice; 99.0% walked during labor; 100.0% had the freedom to choose a position during childbirth. It is noteworthy that no woman in this study was submitted to episiotomy, and more than 70.0% were not submitted to any obstetric intervention. Conclusions: the Programa de Residência em Enfermagem (Residency Nursing Program) an important point in the childbirth humanization process is directly associated to the increase in the normal childbirth rates, the highest use on good practices in childbirth care, and the reduction on obstetric interventions.